Characteristics of Relationship between Executive and Legislative Branches of Power in Israel - A. I. Malamud (Московский журнал международного права, 2012)
The article is dedicated to characteristics of relationship between executive and legislative branches of power in Israel where the Government of the Country has a big influence on Parliament functioning during all the history of the State. The topicality is stipulated by examination in the article of new suggestions, implementation of which could improve the effectiveness of parliamentary control over the activities of the Government.